CXCL1 promotes tumor growth through VEGF pathway activation and is associated with inferior survival in gastric cancer. Issue 2 (10th April 2015) - Wei, Zhe-Wei; Xia, Guang-Kai; Wu, Ying; Chen, Wei; Xiang, Zhen; Schwarz, Roderich E.; Brekken, Rolf A.; Awasthi, Niranjan; He, Yu-Long; Zhang, Chang-Hua
Highlights: The precise role and mechanism of CXCL1 on gastric tumor growth remain unclear. CXCL1 is overexpressed in gastric cancer (GC) and correlates with tumor stage and patient survival. CXCL1 enhances VEGF expression through the activation of JAK2-STAT3 signaling. CXCL1 promotes tumor growth and angiogenesis through the VEGF pathway. The CXCL1/CXCR2 pathway might be a promising therapeutic target in GC. Abstract: The chemokine (C-X-C motif) ligand 1 (CXCL1) regulates tumor–stromal interactions and tumor invasion. However, the precise role of CXCL1 on gastric tumor growth and patient survival remains unclear. In the current study, protein expressions of CXCL1, vascular endothelial growth factor (VEGF) and phospho-signal transducer and activator of transcription 3 (p-STAT3) in primary tumor tissues from 98 gastric cancer patients were measured by immunohistochemistry (IHC). CXCL1 overexpressed cell lines were constructed using Lipofectamine 2000 reagent or lentiviral vectors. Effects of CXCL1 on VEGF expression and local tumor growth were evaluated in vitro and in vivo . CXCL1 was positively expressed in 41.4% of patients and correlated with VEGF and p-STAT3 expression. Higher CXCL1 expression was associated with advanced tumor stage and poorer prognosis. In vitro studies in AGS and SGC-7901 cells revealed that CXCL1 increased cell migration but had little effect on cell proliferation. CXCL1 activated VEGF signaling in gastric cancer (GC) cells, which was inhibited by STAT3 or chemokine (C-X-C motif) receptor 2 (CXCR2) blockade. CXCL1 also increased p-STAT3 expression in GC cells. In vivo, CXCL1 increased xenograft local tumor growth, phospho-Janus kinase 2 (p-JAK2), p-STAT3 levels, VEGF expression and microvessel density. These results suggested that CXCL1 increased local tumor growth through activation of VEGF signaling which may have mechanistic implications for the observed inferior GC survival. The CXCL1/CXCR2 pathway might be potent to improve anti-angiogenic therapy for gastric cancer.